A customized strategic planning framework for oil companies - Khanifar, Abbas (2013)
This is a study on strategic management process in the oil and gas industry, which is an integral part of running such business. The main focus of the research is to find the answer to these questions: What does a typical oil companies' value chain look like? What are the critical success factors of oil companies? What is the relative importance of key success factors? and , what are the typical strategies that work well in oil companies?